Written communication in entrepreneurship course in Malaysian vocational colleges: a qualitative inquiry - Mohamad, Hamidah; Idrus, Faizah (Global Academic Excellence (M) Sdn Bhd (GAE), 2019)
Entrepreneurship curriculum has been implemented in recent years in Malaysian vocational colleges as a platform to expose school leavers to entrepreneurship skills and provide them the basic know-how needed to engage in an entrepreneurial career. Among this knowledge is written communication which involves the skill of preparing the necessary documents and correspondence in a start-up business. However, research findings indicate that very little is known about Malaysian vocational college graduates’ competency in this area after completing the entrepreneurship course. Moreover, existing studies show significant weaknesses or a lack of competency in communication skills, including writing among our graduates. This study aims to explore the implementation of written communication components taught in the entrepreneurship course in Malaysian vocational colleges by examining its curriculum content and teaching approaches utilised in the course. The study applied the qualitative approach using semi-structured interviews and document analysis to gather the data. 15 instructors from 10 vocational colleges located throughout Peninsular Malaysia participated in the interviews. Meanwhile, the document analysis included a course description, modules, teaching plan, lecture notes, coursework, and assignments as well as assessment materials of the course. The results revealed that the business plan model is applied to form the fundamental structure of the written communication component in the entrepreneurship course. However, several key challenges were found in its implementation, including the ambiguity and inconsistency in the key focal point within the written communication knowledge area. Additionally, short and inconsistent course delivery periods were also identified as barriers to effective implementation of the target knowledge as well as the course in general.